2017
DOI: 10.1002/cctc.201601623
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum Location and Acid Strength in an Aluminum‐Rich Beta Zeolite Catalyst: A Combined Density Functional Theory and Solid‐State NMR Study

Abstract: Density functional theory was performed to investigate the specific Al distribution and the origination of Brönsted acid strength in the Al‐rich Beta zeolite catalyst. The most preferable sites for Al atoms of Al‐rich and Si‐rich Beta zeolites represented by 1Al and 2Al atoms are compared by electrostatic potential analysis and substitution energies. IT1 and T9 sites are the most favorable locations for 1Al distribution, while 5MR1‐T92, 5MR2‐T15 and 6MR1‐T66 sites are inclined to be occupied by Al atoms for 2A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 52 publications
3
29
0
Order By: Relevance
“…As demonstrated in our previous report, [40] the strength of the Brönsted acid in the samples can be detected by 1 H MAS NMR after d5-pyridine adsorption. In Figure 8 the 1 H MAS NMR spectra after pyridine adsorption show that the δ 1 H located at 12 ppm is for HBeta zeolite.…”
Section: Acidity Characterization By 1 H Mas Nmrsupporting
confidence: 60%
See 1 more Smart Citation
“…As demonstrated in our previous report, [40] the strength of the Brönsted acid in the samples can be detected by 1 H MAS NMR after d5-pyridine adsorption. In Figure 8 the 1 H MAS NMR spectra after pyridine adsorption show that the δ 1 H located at 12 ppm is for HBeta zeolite.…”
Section: Acidity Characterization By 1 H Mas Nmrsupporting
confidence: 60%
“…The data above underscore that the type of catalyst influences the reaction activity, especially selectivity to p ‐xylene; this may be due to differences in acidity. As a reliable and sensitive approach to directly identify hydroxyl groups in solid acid catalysts, 1 H MAS NMR spectroscopy can offer quantitative information on the hydroxyl protons acting as catalytically‐active Brönsted acid sites [39,40] . The 1 H MAS NMR spectra of the H‐Beta zeolite and MCM‐41 samples before and after functionalization are shown in Figure 7(a).…”
Section: Resultsmentioning
confidence: 99%
“…), may be present in a porous solid as well as in a probe molecule ( 1 H, 13 C, 15 N, and 31 P), ssNMR spectroscopy can be used as an ideal tool to study concentration, distribution, nature and strength of acid sites (Brønsted and Lewis). Alternatively, Lewis acidic sites can be directly detected by multinuclear ( 27 Al, 119 Sn and 47,49 Ti) NMR spectroscopy, which can distinguish between framework and extra-framework species. [100][101][102] Additional information on these specific applications is given in the ESI.…”
Section: Probe Moleculesmentioning
confidence: 99%
“…DFT calculations in combination with ssNMR spectroscopy were implemented to investigate the specific aluminium location and the origin of Brønsted acid strength in Al-rich as well as Si-rich Beta zeolite catalyst. 49 The Brønsted acid strength was correlated to the Al location at the specific T-site on the zeolitic framework. DFT calculations of proton affinities, NH3 adsorption energies and 1 H chemical shifts of pyridine-d5 adsorption on Al-rich H-Beta revealed that its average Brønsted acid strength was weaker than Si-rich counterpart.…”
Section: Fig 26 Correlations Between 1 H Nmr Chemical Shifts and Thementioning
confidence: 99%
“…Alternatively, symmetry considerations can be used to explore heteroatom distribution in a larger configurational space. [26][27][28][29]31,70 However, in zeolites with high concentrations of heteroatoms even with the use of symmetry and of some ad hoc structurerelated constraints, the number of independent configurations is larger than what is tractable by fully atomistic simulations. Our selection of the aluminogermanate PKU-9 zeolite, will provide here an example on how the structural information regarding the location of the Al atoms will vary according to the approach used as the composition changes from that found experimentally to higher Ge/Al.…”
Section: Introductionmentioning
confidence: 99%